Rare Chromone Derivatives from the Marine-Derived Penicillium citrinum with Anti-Cancer and Anti-Inflammatory Activities - Yi-Cheng Chu; Chun-Hao Chang; Hsiang-Ruei Liao; Ming-Jen Cheng; Ming-Der Wu; Shu-Ling Fu; Jih-Jung Chen (Marine Drugs, 2021)
Three new and rare chromone derivatives, epiremisporine C (1), epiremisporine D (2), and epiremisporine E (3), were isolated from marine-derived Penicillium citrinum, together with four known compounds, epiremisporine B (4), penicitrinone A (5), 8-hydroxy-1-methoxycarbonyl-6-methylxanthone (6), and isoconiochaetone C (7). Among the isolated compounds, compounds 2–5 significantly decreased fMLP-induced superoxide anion generation by human neutrophils, with IC50 values of 6.39 ± 0.40, 8.28 ± 0.29, 3.62 ± 0.61, and 2.67 ± 0.10 μM, respectively. Compounds 3 and 4 exhibited cytotoxic activities with IC50 values of 43.82 ± 6.33 and 32.29 ± 4.83 μM, respectively, against non-small lung cancer cell (A549), and Western blot assay confirmed that compounds 3 and 4 markedly induced apoptosis of A549 cells, through Bcl-2, Bax, and caspase 3 signaling cascades.